Table of Content - - (Journal of Humanities & Social Sciences, 2025)
Table of Content: 1. The Role of University Environment and Student Activities in Promoting Citizenship Values among Students of the University of Nizwa as Perceived by Its Students and Staff: A Field Study during the 2010–2011 Academic Semester Ms. Aisha Khalfan Al -Waheibi 2. Institutional Communication in the Digital Age: Innovative Strategies for Deepening Public Engagement through the Synergy of Knowledge Management and Innovation Dr. Mohamed Ouldhali 3. Scientific Research Methodology in Exploratory Qualitative Studies: Methods, Approaches, and Tools Dr. El-Yazidi Reda 4. The Quality of University Services and Its Relationship to Academic Efficiency: A Study on a Sample of Female Students in the Social Work Department at Umm Al-Qura University in Makkah Dr. Rawan Ibrahim Alnasser 5. The role of international intervention in defeating terrorism: (the sahel region as a case study) Ms. Mayssaa Nawaf Abdul-khalek 6. Obstacles to the Arab knowledge industry from the perspective of researchers at King Khalid University Ms. Norah Ali Al-Shahri, Dr. Haya Mohammed Al-Shahri 7. Study of the spatial suitability of commercial pharmacies in Hail city using geographic information systems (GIS) Ms. Asalah Maza Alshurayhi